Quantum dialogue protocol based on self-dual quantum low density parity check codes - Fen LIU; Zhenxing HE; Pengao XU; Hongyang MA (网络与信息安全学报)
In quantum channels,particles are usually affected by noise during transmission.A quantum dialogue protocol based on self-dual quantum low density parity check codes was proposed to resist noise attacks.A combination of B construction method and U construction method was used to construct a self-dual quantum low density parity check matrix.The proposed quantum dialogue protocol can resist common external attacks,and there was no information leakage,which improved the efficiency of encoding and decoding.The security of quantum dialogue protocol was studied from the perspective of error correction.Security analysis shows that the protocol has sufficient security and can effectively resist common malicious attacks.